2021
DOI: 10.3389/fimmu.2021.732102
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressive Cells Deficient in Liver X Receptor α Protected From Autoimmune Hepatitis

Abstract: Myeloid-derived suppressor cells (MDSCs) emerge as a promising candidate for the immunotherapy of autoimmune hepatitis (AIH). However, targets for modulating MDSC in AIH are still being searched. Liver X receptors (LXRs) are important nuclear receptors linking lipid metabolism and immune responses. Despite the extensive studies of LXR in myeloid compartment, its role in MDSCs is currently less understood. Herein, expression of LXRα was found to be upregulated in AIH patients and colocalized with hepatic MDSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…It has been shown that loss of LXRα/β disrupted the balance of hematopoietic population and increased BM and PB myeloid cell numbers (Rasheed et al., 2018). Others have also shown that loss of LXRα resulted in an increased accumulation of myeloid‐derived suppressor cells (MDSCs) in liver (Li, Lian, et al., 2021), and that activation of LXR decreased MDSC abundance in animal models and in individuals treated in a clinical trial (Tavazoie et al., 2018). We have shown previously a great overlap of MDSCs and OCPs and the osteoclastogenic potential of MDSCs (Cai et al., 2020; Li, Zhao, et al., 2021; Su et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that loss of LXRα/β disrupted the balance of hematopoietic population and increased BM and PB myeloid cell numbers (Rasheed et al., 2018). Others have also shown that loss of LXRα resulted in an increased accumulation of myeloid‐derived suppressor cells (MDSCs) in liver (Li, Lian, et al., 2021), and that activation of LXR decreased MDSC abundance in animal models and in individuals treated in a clinical trial (Tavazoie et al., 2018). We have shown previously a great overlap of MDSCs and OCPs and the osteoclastogenic potential of MDSCs (Cai et al., 2020; Li, Zhao, et al., 2021; Su et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we have recently shown that chronic Pg infection significantly downregulates the gene expression of ApoE, a transcriptional target of LXRs, in OCPs (Zhao et al., 2020). In addition, others have shown that LXRs are important for maintaining the balance of hematopoietic populations (Rasheed et al., 2018) and the abrogation of LXRs increases the number of myeloid progenitor populations (Li, Lian, et al., 2021). These data suggest that LXRs are involved in the modulation of OCPs.…”
Section: Introductionmentioning
confidence: 99%
“…Elimination of LXRα promotes amplification of MDSCs by downregulating IRF-8 to significantly ameliorate hepatic immune injury. 59 Deletion of RIP3 showed similar protective effects. RIP3 inhibition led to an increase in CD11b+Gr1+ MDSCs with immunomodulatory properties in the liver, spleen and peripheral blood.…”
Section: Mdscs and Autoimmune Liver Diseasementioning
confidence: 76%
“…Liver X receptors (lxRs), key nuclear receptors linking lipid metabolism and immune responses are upregulated in patients with AIH and co‐localize with hepatic MDSCs. Elimination of LXRα promotes amplification of MDSCs by downregulating IRF‐8 to significantly ameliorate hepatic immune injury 59 . Deletion of RIP3 showed similar protective effects.…”
Section: Current Status Of Research On Mdscs In Liver Diseasementioning
confidence: 93%
“…In addition to macrophages, NKT, NK, T cells, and myeloid-derived suppressor cells play important roles in acute liver injury. [39][40][41] Hence, the proportions of NKT (CD3 + NK1.1 + ), NK (CD3 − NK1.1 + ), T (CD3 + NK1.1 − ), and myeloid-derived suppressor cells (MDSCs, CD11b + Gr-1 + ) cells in the liver were measured using flow cytometry (detailed flow gate strategies are shown in Figure S8). The percentage of activated NKT, NK, and T cells increased following the Con A injection.…”
Section: Il-28a Deficiency Regulated M1 Macrophage Activation In Con ...mentioning
confidence: 99%